An Overview of Surface Water Quality Influenced by Suspended Solid Content in the Sayung Waters, Demak, Indonesia - Ulung Jantama Wisha; Koko Ondara; Gunardi Kusumah (Pusat Riset Kelautan, 2017)
Abrasion which is occurred in the Sayung coast is triggered by a big role of climate change as well as the sea level rise and land subsidence. Resulting degradation ultimately affects changes in existing environmental conditions. This study has aim to determine the existing water based on biological and chemical content which is affected by increasing suspended solid content in the Sayung waters. Purposive sampling technique was applied, and data is analyzed both statistically and spatially. Suspended solid value has ranged 23,1-199,6 mg/L. Distribution of suspended solid was only simulated during low tide towards high tide phase with current speed has ranged 0-0.41 m/s. We found that dissolved oxygen value is quite high in several observation stations which indicates the fertile area with low pollution and blooming tendency. In the station which is dominated by a high suspended solid and turbidity found that the chlorophyll-a decreases. The increased rate of suspended solid is directly enhancing the turbidity and indirectly declines the photosynthesis activity and inhibits the oxygen cycle. Resulting in the primary productivity reduction in the Sayung waters